Silver linings: a personal memoir about Hurricane Katrina and fungal volatiles - Bennett, Joan W. (Frontiers in Microbiology, 2015)
In the aftermath of Hurricane Katrina, the levees protecting New Orleans, Louisiana failed. Because approximately 80% of the city was under sea level, widespread flooding ensued. As a resident of New Orleans who had evacuated before the storm, and a life-long researcher on filamentous fungi, I had known what to expect. After the hurricane I traveled home with a suitcase full of Petri dishes and sampling equipment so as to study the fungi that were “eating my house.” Not only were surfaces covered with fungal growth, the air itself was full of concentrated mold odor, a smell that was orders of magnitude more funky than any damp, musty basement I had ever encountered. The smell made me feel bad and I had to take regular breaks as I sampled. Being a mycotoxin expert, I knew a fair amount about “sick building syndrome” but believed that it was difficult to get enough respiratory exposure to toxins to cause the array of symptoms associated with the syndrome. So why was I feeling sick? Some Scandinavian experts had hypothesized that mold volatile organic compounds (VOCs) might be the fungal metabolites to blame for sick building syndrome and the time in my smelly, mold infested home made me think they might be right. After securing a new job and establishing a new laboratory, I endeavored to test the hypothesis that some volatile mold metabolites might be toxic. My laboratory at Rutgers University has interrogated the role of VOCs in possible interkingdom toxicity by developing controlled microcosms for exposing simple genetic model organisms to the vapor phase of growing fungi. Both Arabidopsis thaliana and Drosophila melanogaster exhibit a range of toxic symptoms that vary with the species of fungus, the duration of exposure, and other experimental parameters. Moreover, low concentrations of chemical standards of individual fungal VOCs such as 1-octen-3-ol also exhibit varying toxicity and cause neurotoxicity in a Drosophila model.